Adhocracy as a Model for Organizing Government Institution in Simplifying Indonesian Bureaucracy - Irwansyah Irwansyah (Puslatbang KDOD Lembaga Administrasi Negara, 2021)
The Presidential Regulation instigated this research to simplify the Bureaucracy with only two positions in government organisations. Accountability, position, work complexity, authority, coordination mechanism, organizing, and work system can induce several problems when this regulation is implemented. This research aims to critically explore the model for organizing government institutions in simplifying Bureaucracy. This research employed PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). This research shows that the adhocratic organisation model as the antithesis of Bureaucracy by creating several task groups coordinated by the highest functionary position, reconfiguring the management of functionary position, and applicating business process are recommendations to anticipate problems emerging from simplifying Bureaucracy. But, not all government functions can be made adhocratic, and it is also crucial to understand that the management and leaders need to departmentalise in simplifying Bureaucracy meticulously.